CHANGES IN CARBOHYDRATE CONTENT IN THE SEEDS OF SCHLEICHERA OLEOSA (KUSUM) DUE TO BIODETERIORATION BY PATHOGENIC FUNGI DURING STORAGE - A. K. SRIVASTAVA; S. KUMAR; G. K. PANDEY (The Bioscan, 2011)
The unsanitary and humid condition during storage of seeds of Schleichera oleosa f. Sapindaceae (Kusum) makes it prone to a faster biodeterioration due to colonization of mycoflora namely Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger, Fusarium solani, paccilomyces variotii and mucar spp. These internal mycodwellers significantly decreased the carbohydrate content in comparison with the control group not infested with the fungi. In their prolonged association with the seeds for one year the glucose level dropped by as much as 50.15% of its initial value while control group by just 2.15%. Similarly, total sugar also registered a loss of 40.25 per cent with control group at 1.48 per cent. The starch in the stored seeds reduced steadily by 48.88% but the control group lost only 2.04%.